El primer año de la pandemia – ¿Qué hemos aprendido del SARS-CoV-2/COVID-19? - Rodriguez-Morales, Alfonso J.; Rosero-Oviedo, Carlos Andres; Perea-Padilla, Laura Cristina; Ramírez-Osorio, Maria Juliana; Bonilla-Aldana, D. Katterine; Cardona-Ospina, Jaime A.; Villamil-Gómez, Wilmer E. (Revista del Cuerpo Médico Hospital Nacional Almanzor Aguinaga Asenjo, 2021)
Editorial (Sin resumen)